Gonad morphogenesis and distal tip cell migration in the Caenorhabditis elegans hermaphrodite - Wong, Ming-Ching (2012)
Cell migration and morphogenesis are key events in tissue development and organogenesis. In Caenorhabditis elegans, the migratory path of the distal tip cells determines the morphology of the hermaphroditic gonad. The distal tip cells undergo a series of migratory phases interspersed with turns to form the gonad. A wide variety of genes have been identified as crucial to this process, from genes that encode components and modifiers of the extracellular matrix to signaling proteins and transcriptional regulators. The connections between extracellular and transmembrane protein functions and intracellular pathways are essential for distal tip cell migration, and the integration of this information governs gonad morphogenesis and determines gonad size and shape.